2018
DOI: 10.3389/fmicb.2018.00875
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Infectivity Against Pseudomonas aeruginosa in Saline Conditions

Abstract: Pseudomonas aeruginosa is a ubiquitous member of marine biofilm, and reduces thiosulfate to produce toxic hydrogen sulfide gas. In this study, lytic bacteriophages were isolated and applied to inhibit the growth of P. aeruginosa in planktonic mode at different temperature, pH, and salinity. Bacteriophages showed optimal infectivity at a multiplicity of infection of 10 in saline conditions, and demonstrated lytic abilities over all tested temperature (25, 30, 37, and 45°C) and pH 6–9. Planktonic P. aeruginosa e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Acinetobacter genus, namely A. modestus, A junii and A. seohaensis were isolated from the influent of the KAUST wastewater treatment plant as described before (21) and propagated by the double layer method (48). A detailed description of bacteriophages isolation can be found in supporting information, section "Bacteriophages isolation".…”
Section: Bacteriophages Isolation and Characterization Bacteriophagementioning
confidence: 99%
See 3 more Smart Citations
“…Acinetobacter genus, namely A. modestus, A junii and A. seohaensis were isolated from the influent of the KAUST wastewater treatment plant as described before (21) and propagated by the double layer method (48). A detailed description of bacteriophages isolation can be found in supporting information, section "Bacteriophages isolation".…”
Section: Bacteriophages Isolation and Characterization Bacteriophagementioning
confidence: 99%
“…Besides infecting their intended bacterial host, bacteriophages can also induce the release of enzymes that degrade the EPS biofilm matrix, in turn, increasing biofilm susceptibility to biocides (20). Moreover, bacteriophages are able to infect bacteria over a broad range of pH, salinity and temperature (21). For these reasons, bacteriophages were also applied as a biological-based approach to reduce membrane biofouling (22), albeit mainly demonstrated against single-species biofilms (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…quorum quenching and phage-based decomposition). [10][11][12] In particular, coating heavy metal nanoparticles on the surface of membranes demonstrated promising results. An earlier study demonstrated that polysulfone membranes impregnated with silver (Ag) nanoparticles showed not only high antibacterial properties but also improved biofouling resistance.…”
Section: Introductionmentioning
confidence: 99%